TPCS/PBAT blown extruded films added with curcumin as a technological approach for active packaging materials - Campos, Sabrina Silva de (2018)
The development of active packaging is a relevant topic demanding the development of films with diverse properties to preserve specific foodstuff. The objective of this work was to obtain extruded TPCS/PBAT films containing curcumin and evaluate it as an active antimicrobial and antioxidant packaging to protect chia oil from oxidative degradation. Morphology, thermal, mechanical, antimicrobial, and antioxidant evaluation of the films were conducted to determine whether the presence of curcumin affected the film’s properties. Infrared Spectroscopy indicated that curcumin addition affected the crosslinking reaction between citric acid and starch, which explains the changes in hydrophilicity and mechanical strength of the films. The incorporation of curcumin conferred antimicrobial activity against Gram-positive (Staphylococcus aureus) and Gram-negative (Pseudomonas aeruginosa and Escherichia coli) bacteria, as well as antioxidant activity. Films were tested as chia oil packaging, being verified that they successfully prevented oil degradation under accelerated stability test (60 °C for 7 days), demonstrating the feasibility of using TPCS/PBAT biodegradable films containing curcumin to obtain active packaging materials.